Passivity-based consensus and passification for a class of stochastic multi-agent systems with switching topology - Hu, Guoqiang (2013)
This paper studies the passivity-based consensus analysis and the consensus synthesis problem (called passification) for a class of stochastic multi-agent systems subject to external disturbances. Based on Lyapunov methods, graph theory, and slack matrix methods such as the free-weighting matrix and Jensen's integral inequality, a new storage Lyapunov functional is proposed to derive delay-dependent sufficient conditions on mean-square exponential consensus and stochastic passivity for the stochastic multi-agent systems. By proposing passive time-varying stochastic consensus protocols, the solvability conditions for the passification problem are derived based on linearization techniques. A numerical example is provided to illustrate the effectiveness of the theoretical results.